After Pettenkofer. Munich's Institute of Hygiene and the long shadow of National Socialism, 1894-1974 - Mathias Schütz (Elsevier, 2020)
The year 2019 marked the 140th anniversary of the inauguration of the first Institute of Hygiene, which was established for Max von Pettenkofer at the university of Munich. After Pettenkofer, his successors tried to advance the science of hygiene each in their own specific way, highlighting different aspects and trying to relate them to Pettenkofer's legacy: Max von Gruber promoted an understanding of hygiene which was more and more tied to constitutional and racial factors, Karl Kisskalt tried to revise a perceived bacteriological paradigm, and Hermann Eyer focused on preventive public health measures. All of those influences had a more or less explicit and distinct connection to the general development of German medicine in the first half of the 20th century and its culmination in National Socialist crimes. The history of Munich's Institute of Hygiene after Pettenkofer illustrates the differing scientific and ideological paths this development pursued by the examples of its three long-term protagonists and their relationship to National Socialism.